Funciona la gamificación en la educación? Evidencia experimental de Chile - Roberto Araya; Elena Arias Ortiz; Nicolas L. Bottan; Julian Cristia (Inter-American Development Bank (IDB), 2019)
– Gamification, or the introduction of game elements to non-game contexts, has the potential to improve learning by increasing student motivation. However, there is little rigorous evidence about its effectiveness. In this paper, we experimentally evaluate an innovative technology program that uses gamification to increase math learning in low-performing primary schools in Chile. The ConectaIdeas program involves two weekly sessions in a computer lab during which students use an online platform to solve math exercises. The platform tracks how many exercises students perform and features different types of individual and group competitions to promote student motivation. Results indicate large positive effects on math learning of about 0.27 standard deviations on the Chilean national standardized exam (no effects were found on language). The program also affected several non-academic outcomes in both positive and negative ways. On the one hand, it increased students' preference to use technology for math learning and promoted the idea among students that study effort can raise intelligence. On the other hand, the program increased math anxiety and reduced students' preferences to collaborate in teams. These results suggest that gamification could be an important tool to boost student learning, but that it may bring unintended consequences.
Keywords: I21; I28; 330; Education; Gamification; Technology; Experiments